Esophageal reconstruction by colon interposition after esophagectomy for cancer analysis of current indications, operative outcomes, and long‐term survival. Issue 2 (24th December 2015) - Reslinger, Vincent; Tranchart, Hadrien; D'Annunzio, Elsa; Poghosyan, Tigran; Quero, Laurent; Munoz‐Bongrand, Nicolas; Corte, Helene; Sarfati, Emile; Cattan, Pierre; Chirica, Mircea
Abstract : Introduction: Colon interposition is an alternative solution for esophageal reconstruction if the stomach cannot be used. The study reviews current indications and results of coloplasty for cancer. Methods: Patients who underwent colon interposition for gastro‐esophageal malignancy were included. Primary coloplasty was defined as upfront colon interposition. Salvage coloplasty was defined as colon interposition after primary reconstruction failure. Mortality, morbidity, function, and survival were evaluated. Results: We included 28 patients (24 men, median age 61 years). Ten (36%) patients underwent primary coloplasty due to previous gastrectomy (n = 5), conduit gastric cancer (n = 2), extensive gastroesophageal involvement (n = 2), and gastric cancer recurrence (n = 1). Salvage coloplasty was performed in 18 (64%) patients for postoperative graft necrosis (n = 5) and intractable strictures (n = 3). Operative mortality, morbidity, and graft necrosis rates were 14% (4/28), 86% (24/28), and 14% (4/28), respectively; there were no significant differences between primary and salvage coloplasty. Survival rates at 1‐, 3‐, and 5 years were 81%, 51%, and 38%, respectively. Survival was decreased after primary coloplasty when compared to salvage coloplasty ( P  = 0.03). Nine patients experienced tumor recurrence (primary: n = 6, salvage: n = 3) after coloplasty and eight of them died. Conclusion: Colon interposition after esophagectomy is a useful but morbid endeavor. Colon interposition as salvage therapy is associated with improved survival compared to its use as primary esophageal replacement, and colon interposition in the latter cohort should be used with caution due to poor cancer‐specific survival in this patient population. J. Surg. Oncol. 2016;113:159–164 . © 2015 Wiley Periodicals, Inc.